Xerox Corporation : developing a new image - Lamb, Amanda M.; Elston, Lauren P.; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
After an extensive study, Xerox decided to undergo a rebranding. After unveiling a new logo, the challenge is to A) roll out the new logo, B) change perception that Xerox only makes copiers, and C) demonstrate that the rebranding was worth the multimillion dollar investment.
Originally published: Lamb, A.M., Elston, L.P., & ORourke, J. S. (2008). Xerox Corporation: Developing a new image. 08-12. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Xerox Corporation; Copying machine industry -- Marketing